Heat capacities : liquids, solutions and vapours - Letcher, T. M.; Wilhelm, Emmerich (Royal Society of Chemistry, 2010)
The book contains the very latest information on all aspects of heat capacities related to liquids and vapours.
Keywords: Thermochemistry.; Liquids -- Thermal properties.; Vapors -- Thermal properties.; elektronické knihy; electronic books